Nikmatnya tasawuf : mengupas kisah sukses ulama tasawuf dalam Islamisasi Nusantara - Darmawijaya, 1974- (Makassar : Pustaka Refleksi, 2008)
Sufism and history of Islam in Indonesia.
Includes bibliographical references (p. 93-96).
Keywords: Sufism -- Indonesia; Islam -- Indonesia -- History